SYMBOLISM AND CULTURAL IMAGERY IN ULUGBEK HAMDAM’S WORKS - Babaxanov Laziz Abdullaxanovich (International Scientific and Current Research Conferences, 2024)
Ulugbek Hamdam, a celebrated figure in modern Uzbek literature, is renowned for his use of rich symbolism and cultural imagery, which convey complex emotions, ideas, and cultural values. This article explores how Hamdam employs metaphorical language to infuse his poetry and prose with symbols drawn from Uzbek cultural heritage, spirituality, and social traditions. His work reflects an intricate layering of meanings that resonates with readers, illuminating aspects of identity, tradition, and national ethos. Through an analysis of Hamdam’s key works, this article seeks to uncover the role of symbolism and cultural imagery in his writing, exploring how these literary devices enhance thematic depth and connect his audience to a shared cultural consciousness. Ultimately, this study provides insights into how Hamdam’s literary artistry contributes to the preservation and evolution of Uzbek cultural identity.